Analisis Potensi Material Silisena-Ni dalam Menyerap Gas Emisi CO, NO, NO2, dan NH3 Menggunakan Pendekatan Simulasi Kuantum - Zulaehah, Siti; Yasinta, Syaukaty; Fachrudin, Muhammad; Nuraini, Alfiah Zahro (Creative Research in Engineering (CERIE), 2025)
Air pollution caused by emission gases such as carbon monoxide (CO), nitrogen monoxide (NO), nitro- gen dioxide (NO2), and ammonia (NH3) has become a major challenge in emission technology development within the industrial sector and human health protection. The development of efficient gas adsorption materials is an essential solution to reduce the atmospheric concentration of these harmful gases. In this study, the potential of nickel-doped silicene (Ni-doped silicene) as a gas adsorbent material was analyzed using a quantum simulation approach based on Density Functional Theory (DFT). The geometric struc- tures of Ni-doped silicene-gas complexes were fully optimized to evaluate key adsorption parameters, including adsorption energy, bond distance, and charge redistribution. The results indicate that Ni dop- ing introduces active sites on the silicene surface, significantly enhancing chemical interactions with all target gas molecules. Negative adsorption energies were observed across all systems, following the inter- action strength order: NO > NO2 > CO > NH3, indicating stable and exothermic binding processes. The strongest interaction occurred at the top Ni site, where hybridization between Ni d-orbitals and molecular orbitals of the gas molecules led to significant charge transfer and electronic property modification. Band structure and DOS analyses revealed Fermi level shifts and the opening of an energy gap after adsorption, suggesting a transformation of the material’s characteristic from semimetallic to semiconducting. With high energetic stability and selective affinity toward toxic gases, Ni-doped silicene demonstrates great potential as a gas-capturing or sensing material for industrial emission control applications Keywords: Silicene, Ni-doping, gas adsorption, DFT, emission control, 2D materials